Somatic Embryogenesis Induction in Narcissus papyraceus cv. Shirazi (Plant Tissue Culture and Biotechnology, 2008)
Explants from bulb scales of Narcissus papyraceus cv. Shirazi cultured in MS and Nitsch media containing different concentrations of BAP, 2,4-D, GA3, Kn, IBA and NAA produced highest number of regenerated bulblets in Nitsch medium containing BAP (2.2 mg/l) and 1.1 mg/l 2,4-D. The highest number of direct somatic embryos were observed in MS containing 0.5 mg/l GA3, 1.6 mg/l BAP and 1.6 mg/l 2,4-D. Induced somatic embryos were multiplied by transferring them to hormone free MS.Key words: Narcissus, Somatic embryogenesis, RegenerationDOI = 10.3329/ptcb.v17i1.1119Plant Tissue Cult. & Biotech. 17(1): 37-46, 2007 (June)